Biosimilars: development and investigation using achievements in modern biotechnology - R. R. Niyazov; M. A. Dranitsyna; A. N. Vasiliev; E. V. Gavrishina (Сахарный диабет)
Biosimilars are biological drug products that have an equivalent clinical profile with innovator biotherapeutics but are developed under a reduced program. To this end, specific comparability approaches are followed based on reverse engineering that involves a thorough analysis of the innovator biotherapeutics and the development of the version of the latter, which should be as much as possible similar with respect to structural and functional characteristics with the innovator. This approach includes the evaluation and comparison between the biosimilar and innovator biologic with respect to the molecular structure and impurity profile and of biological activity in in vitro settings as well as pharmacokinetic, pharmacodynamic, and immunogenicity characteristics on human subjects. Where considered necessary, animal studies or phase 3 clinical studies might be performed when residual uncertainties remain in terms of biosimilarity, that could not have been resolved in the previous tests and trials. Any potentially inevitable differences should be insignificant for safety and efficacy. The state-of-the-art methods of biotechnology and analytics, when applied in line with the appropriate scientific and regulatory requirements, can allow developing similar biologics where no difference in the clinical profile exists with the respective innovator product. Available experience demonstrates the lack of major problems due to the incomparability between the biosimilar and corresponding reference biologics when applicable scientific standards and regulatory recommendations are met.